Effects of anthocyanidins and anthocyanins on the expression and catalytic activities of CYP2A6, CYP2B6, CYP2C9, and CYP3A4 in primary human hepatocytes and human liver microsomes - Srovnalova, Alzbeta; Svecarova, Michaela; Kopečná Zapletalová, Michaela; Anzenbacher, Pavel; Bachleda, Petr; Anzenbacherová, Eva; Dvořák, Zdeněk (Journal of agricultural and food chemistry, 2014)
Anthocyanidins and anthocyanins are pharmacologically active constituents of various berry fruits, such as blueberry and cranberry. These compounds are also contained in massively used nutritional supplements based on extracts or dry matter from berry fruits. The current study evaluated the effects of anthocyanidins and anthocyanins on the expression and catalytic activity of major drug-metabolizing enzymes CYP2C9, CYP2A6, CYP2B6, and CYP3A4 in primary cultures of human hepatocytes and human liver microsomes. Expression of mRNA was quantified by qRT-PCR. Expression of proteins was evaluated by Western blotting and immunochemiluminescence. The catalytic activity of CYP enzymes was measured by HPLC using specific enzyme substrates. Tested anthocyanidins (6) and anthocyanins (21) did not induce the expression of mRNA and protein of CYP2C9, CYP2A6, CYP2B6, and CYP3A4 genes in human hepatocytes. Catalytic activities of CYP2C9, CYP2A6, CYP2B6, and CYP3A4 enzymes were inhibited by all anthocyanidins to different extents (e.g., delphinidin inhibits CYP3A4 by >90% at 100 μM with IC50 = 32 μM). Of 21 anthocyanins tested, only cyanidin-3-O-rhamnoside (CYP3A4 by >75% at 100 μM with IC50 = 44 μM) and two glycosides of delphinidin significantly inhibited examined cytochromes P450. It may be concluded that in the ranges of common ingestion of either food or dietary supplement an induction or significant inhibition of CYP2C9, CYP2A6, CYP2B6, and CYP3A4 activity is most probably not expected.
Keywords: hepatocyty; Microsomes, Liver; cytochrom P-450 CYP3A; Biocatalysis; rostlinné extrakty; anthokyaniny; brusnice s jedlými plody; Gene Expression Regulation, Enzymologic; Blueberry Plants; cytochrom P450 CYP2B6; Cytochrome P-450 CYP2B6; Hepatocytes; cytochrom P450 CYP2C9; Plant Extracts; lidé; Cytochrome P-450 CYP2C9; Cytochrome P-450 CYP3A; Humans; regulace genové exprese enzymů; biokatalýza; Vaccinium macrocarpon; Anthocyanins; jaterní mikrozomy